Differences In Coping Stress Strategies Of Psychology Students From The 2022 Class Of Fipp Unima Who Participated In The Mbkm Internship Based On Gender - Chafa Gloria Lela; Meike E. Hartati; Veronika J. Kamasi (International Journal of Technology and Education Research, 2026)
In early adulthood, students are faced with various academic and non-academic demands that can trigger stress. In facing these conditions, students certainly have their own ways of responding. Stress coping strategies are an important aspect in helping students manage the pressure they experience so they can continue to function optimally. Stress coping strategies consist of three types: problem-focused coping, emotional-focused coping, and less useful coping, the use of which can be influenced by various factors, one of which is gender. This study aims to determine differences in stress coping strategies in Psychology students class of 2022 based on gender. This study used a quantitative approach with a comparative method. The study sample consisted of 135 students, consisting of 39 male students and 96 female students. The research instrument used a Likert scale. Data analysis was conducted using an independent sample t-test. The results obtained showed a significance value of 0.025 (p <0.05), thus finding significant differences in stress coping strategies based on gender. Female students had a higher average stress coping score (M= 51.37) than male students (M= 49.90). Therefore, it can be concluded that there are significant differences in stress coping strategies based on gender among psychology students from the 2022 intake of FIPP Unima who participated in the MBKM internship, with female students having a higher average score than male students.